Some legal problems of rational use of pasture land in the Republic of Kazakhstan - Yerkinbayeva, L.K.; Ozenbayeva, A.T.; Saipinov, D.R. (Bulletin of the Karaganda University “Law Series”, 2022)
The purpose of the proposed research is to comprehensively study the legal problems of pasture use in the current conditions of the constitutional reform in Kazakhstan, during which the main priority of the country is the use of land in the interests of the people of the country, the development of scientifically based theoretical provisions and practical recommendations for improving the current legislation of the Republic of Kazakhstan. At present, neither state bodies nor legal science can give unambiguous answers to the pressing questions of this problem; there are no special scientific developments on this problem. The legislation of the Republic of Kazakhstan on pastures itself is at the stage of formation, and the problems of their rational use and protection have not received appropriate legal regulation. The lack of a clear regulation of the conduct of economic activities of personal subsidiary farms of citizens (hereinafter referred to as PSF) has led to the fact that today we have environmental problems of pasture degradation, an unfavorable epizootic and sanitary situation in settlements and around them. The authors concluded that the current Law «On Pastures» does not take into account the existing problems in settlements, therefore, adjustments to its content and the land legislation of the country are required. It is proposed to detail the legal regime for the use of pastur es that are part of the lands of the forest and water resources, settlements and on the territory of specially protected natural areas. The revival of distant-pasture and semi-transhumant animal husbandry requires the development of legal mechanisms for regulating this sphere of agricultural production, the specification of the regime for the use of distant-pasture and seasonal pastures.